Protocol: A cluster randomised controlled trial of Reciprocal Reading: A teacher training comprehension programme. (2018) - O'Hare, Liam; Stark, Patrick; McConnellogue, Sheila; Lloyd, Katrina; Cockerill, Maria; Biggart, Andy
Highlights: Protocol for a pragmatic randomised controlled trial in 97 primary schools. The intervention aims to improve reading comprehension and overall literacy. The intervention is a teacher training programme for reading comprehension. Abstract: This paper presents the research protocol for a pragmatic RCT of the Reciprocal Reading programme. Reciprocal Reading (RR) is a workforce development programme that supports practicing Teachers/Teaching Assistants develop and deliver comprehension instruction in mainstream UK settings for pupils aged 8–11 years. The protocol outlines a research design that will assess whether the RR programme can improve a number of specific outcomes in intervention group pupils, in a sample of schools experiencing higher than average levels of disadvantage. The primary outcome for analysis is reading comprehension with secondary outcomes of overall literacy, reading accuracy and comprehension pre-cursors at the child and school level. The study will also include a process evaluation using qualitative data and quantitative implementation data.